1982
DOI: 10.1136/pgmj.58.676.115
|View full text |Cite
|
Sign up to set email alerts
|

Primary adenocarcinoma of the duodenum associated with cutaneous neurofibromatosis (von Recklinghausen’s disease)

Abstract: A case of primary adenocarcinoma of the duodenum in a 29-year-old man with neurofibromatosis (von Recklinghausen’s disease) is described. As far as can be ascertained, such an association has not been described before.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…These tumors were located in the ampulla of Vater in five cases (13, 18 -20, and the present one), in the head of the pancreas in four cases (16,(21)(22)(23), in the duodenum in four cases (10,19,22,24), in the bile duct in one case (23), and in the gallbladder in one case (13). From this analysis it emerges that the association of epithelial cancers with NF-1 is equally distributed between the sexes (seven males, five females, and two of unknown sex), in accordance with the general distribution of NF-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These tumors were located in the ampulla of Vater in five cases (13, 18 -20, and the present one), in the head of the pancreas in four cases (16,(21)(22)(23), in the duodenum in four cases (10,19,22,24), in the bile duct in one case (23), and in the gallbladder in one case (13). From this analysis it emerges that the association of epithelial cancers with NF-1 is equally distributed between the sexes (seven males, five females, and two of unknown sex), in accordance with the general distribution of NF-1.…”
Section: Discussionmentioning
confidence: 99%
“…4). The association of an adenocarcinoma of the papilla with dysplasia of the duodenum and of the terminal choledochus (24) and an adenocarcinoma of the pancreas with focal atypical proliferation of the pancreatic ducts (16) have already been described.…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of neurofibromatosis with small-bowel adenocarcinoma is exceedingly rare (Table 1) (Albores-Saavedra et al 1974;Ho et al 1980;McGunchey et al 1982;Nelson 1982;Jones et al 1987;Benharroch et al 1992;Joo et al 2002). A review of the English-language literature disclosed seven reported cases of adenocarcinoma of the small bowel in patients with neurofibromatosis.…”
Section: Discussionmentioning
confidence: 99%
“…7 Subsequently, five patients have been reported with neurofibromatosis and smallbowel adenocarcinoma. [8][9][10][11][12] We report a case of primary duodenal adenocarcinoma in a patient with neurofibromatosis type 1, and review the literature pertaining to this condition.…”
Section: Introductionmentioning
confidence: 99%